The effects of trust on online Malaysian students buying behavior - Zendehdel, Marzieh; Paim, Laily; Bojei, Jamil; Osman, Syuhaily (American-Eurasian Network for Scientific Information, 2011)
The objective of this study is to explore three dimensions of trust that affect consumers’ attitude towards online shopping and online shopping intention in Malaysia. Data was collected from students’ samples in Malaysia. SEM (Structural Equation Model) was used to test the hypotheses and confirmed the fit of the model. The researcher found that there are only two factors for explaining attitude towards online shopping, which are integrity and ability; and there is no significant in consumers’ attitude towards online shopping based on benevolence; however, there is a relationship between attitude toward online shopping and online shopping intention.